Prophylactic and therapeutic HBV vaccination by an HBs‐expressing cytomegalovirus vector lacking an interferon antagonist in mice. Issue 2 (9th November 2020) - Huang, Hongming; Rückborn, Meike; Le‐Trilling, Vu Thuy Khanh; Zhu, Dan; Yang, Shangqing; Zhou, Wenqing; Yang, Xuecheng; Feng, Xuemei; Lu, Yinping; Lu, Mengji; Dittmer, Ulf; Yang, Dongliang; et al.
Abstract: Cytomegalovirus (CMV)‐based vaccines show promising effects against chronic infections in nonhuman primates. Therefore, we examined the potential of hepatitis B virus (HBV) vaccines based on mouse CMV (MCMV) vectors expressing the small HBsAg. Immunological consequences of vaccine virus attenuation were addressed by either replacing the dispensable gene m157 ("MCMV‐HBsȍ) or the gene M27 ("ΔM27‐HBs"), the latter encodes a potent IFN antagonist targeting the transcription factor STAT2. M27 was chosen, since human CMV encodes an analogous gene product, which also induced proteasomal STAT2 degradation by exploiting Cullin RING ubiquitin ligases. Vaccinated mice were challenged with HBV through hydrodynamic injection. MCMV‐HBs and ΔM27‐HBs vaccination achieved accelerated HBV clearance in serum and liver as well as robust HBV‐specific CD8 + T‐cell responses. When we explored the therapeutic potential of MCMV‐based vaccines, especially the combination of ΔM27‐HBs prime and DNA boost vaccination resulted in increased intrahepatic HBs‐specific CD8 + T‐cell responses and HBV clearance in persistently infected mice. Our results demonstrated that vaccines based on a replication competent MCMV attenuated through the deletion of an IFN antagonist targeting STAT2 elicit robust anti‐HBV immune responses and mediate HBV clearance in mice in prophylactic and therapeutic immunization regimes. Abstract : A CMV‐based vector lacking an IFN antagonist and expressing HBsAg elicits robust anti‐HBV immune responses and protects mice against HBV challenge in a prophylactic immunization regime. The vector elicits robust anti‐HBV immune responses and achieves HBV clearance in HBV‐persistent mice in a therapeutic immunization regime.